New perspectives on the IPv6 transition - Dell, Peter (Curtin University of Technology, 2009)
Despite it being more than a decade old, and nearly two decades since the problems with IPv4 were first identified, IPv6 still has not diffused significantly through the Internet. Policies advocating market forces to promote IPv6 diffusion are widespread, and thus this paper examines IPv6 adoption from the perspectives of Hotelling's aconomics of exhaustible resources and the economics of permit markets, concluding in both cases that significant IPv6 diffusion will not occur until after the IPv4 address space is exhausted. This outcome is not desirable, and therefore new policy alternatives must be debated.